(untitled) (Bulletin KNOB, 2024)
Around 2000 years ago peat was present on a vast scale throughout the Dutch lowlands. Over the course of time, however, peat extraction and post-reclamation subsidence led to the disappearance of large volumes of peat. A quarter of the Netherlands ended up below sea level and a variety of peat degradation landscapes emerged: reclaimed peatlands, lakes and drained lakes, tidal inlets and tidal clay polders. Although these typical Dutch lowland landscapes were in large part man-made, the presence of peat played a crucial role in their formation. The spatial distribution of these peat degradation landscapes was to a great degree determined by the natural peat landscape prior to reclamation. The transformation of the peat landscape occurred in three phases. During the first transformation, which began during the Roman period, large areas of peatland, including in Zeeland, the kop van Noord-Holland (the northern tip of North Holland) and parts of the northern Netherlands, turned into tidal clay areas. This was a consequence of early reclamation efforts, which resulted in subsidence and seawater inundation. This was often followed by the formation of tidal areas with shoals and channels. This was a direct consequence of the fragility of the coastal peatland drowning that covered large parts of the coastal plain; the most vulnerable sections were located along a narrow dune strip or near a large inlet. Although some of the submergence was eventually compensated for by sand and clay deposition, large estuaries like the Westerschelde and Oosterschelde are lasting remains of those sea ingressions in former peatlands. From the ninth century onwards, a second major transformation of the coastal peatland landscape occurred, that of large-scale reclamation. Much of the natural marsh vegetation was removed, and the land was drained and used for agriculture. This put an end to natural peat growth and initiated a process of ground subsidence, which soon rendered arable farming impossible. Eventually measures like the damming and diking of watercourses and the draining of polders became necessary. Any peat domes and natural streams tended to have a strong impact on drainage channels and parcellation in reclaimed peatlands. Two thirds of total peat loss in the coastal plain can be attributed to oxidation of the peat following this wave of reclamation activities. Peat also disappeared as a result of lake shore erosion or salt mining. Some major land losses occasionally occurred in the vulnerable embanked peatlands during storm flood events. This was especially the case further inland, such as in the Biesbosch and Dollard areas. A third major transformation began in the fourteenth century with the widespread introduction of the ‘wet’ method of peat extraction using a hand-held ‘scoop’ dredge. Peat extraction occurred in places where sphagnum or sedge peat occurred, which were suitable peat types for burning. Many of the lakes that remained after removal of the peat were later drained again. Together, peat extraction and lake shore erosion accounted for around one third of peat volume loss. Due to these activities, half of the peat volume that was present around the year 1000 has been lost. It is estimated that this loss entailed 3.1 Gt in CO2 emission, making the Netherlands one of the biggest pre-industrial sources of human greenhouse gas emissions. The remaining peat is still present in the reclaimed peatlands, in young marine clay areas and, to a lesser degree, beneath urban areas and dwelling mounds.